The Paddy Cultivation in District of Lower Perak: Traditional Heritage Until 1957 - Fauziah Che Leh, Hairy Ibrahim, Khairi Ariffin, Ramli Saadon, Sahul Hamid Mohamed Maiddin, (Opción, 2019)
The research was carried out to identify the development the paddy planting in the district of Lower Perak during the colonial era in 1900 until 1957. The research was carried out by using qualitative methods by analyzing official colonial documents, annual report and writing on paddy cultivation in Perak. The Results showed that the District of Lower Perak had paddy cultivation area that had been developed during the British colonial era. The new settlement has also been developed due to the increase of paddy planting area and construction of the irrigation system.